Shy Customers Vs Non Shy Customers: Who Does Love More Online Shopping? - Aydin, Oguzhan; Hasiloglu, Selcuk Burak (European Scientific Journal, ESJ, 2017)
Nowadays, almost every market has an intense competition environment. Naturally, in order to survive in such an environment, decision maker must understand accurately their costumer wants and needs, even must generate individual solutions, not only massive. The way to understand costumers is through determining the factors well that affect purchasing decision-making of costumers. An emotion that can directly affect human behaviour such as shyness is a question mark on the frame of consumer behaviour, although purchasing decision-making process is examined with many different approaches. The aim of this study is to illuminate whether shyness has an effect on online purchasing decision-making process or not. In the literature, although a lot of studies have been done about shyness in different fields, a sufficient level of study was not encountered about shyness in the field of marketing. The fact that shyness has not been addressed in terms of marketing, especially on the internet, reveals the importance of this study.